The Nature of Need Structure in Nonwork - Jamal, Muhammad; Baba, Vishwanath; Mitchell, Vance (Relations industrielles / Industrial Relations, 1982)
This study attempts to verify the appropriateness of three existing taxonomies of need fulfillment by Maslow, Alderfer and lawler, respectively, in the area of nonwork.